ABOUT DETAILED FEATURES OF SOLIDWORKS COSTING MODULE - Cătălin IANCU; Yuriy GUTSALENKO (Fiabilitate şi Durabilitate)
In this paperwork is presented some detail features of the SOLDWORKS Costing module. These features allow the designer to make some decisions adjusted for the specific costs of a given production workshop, that can lead to more efficient design and lower costs, being an important activity of CAD/CAE integration in 21-st century CIM (Computer Integrated Manufacturing) production.